2012
DOI: 10.1542/peds.2012-0900r
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorders and Developmental Disabilities in Children From Immigrant Families in the United States

Abstract: OBJECTIVES: Recent census data show that nearly one-quarter of US children have at least 1 immigrant parent; moreover, there has been a dramatic increase in children diagnosed with autism spectrum disorders (ASDs) and select developmental disabilities (DDs). However, little is known about access to medical home and adequacy of insurance coverage for children with ASDs and select DDs from immigrant families.METHODS: By using the 2007 National Survey of Children' s Health, we compared children with ASDs and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 25 publications
(22 reference statements)
1
32
0
Order By: Relevance
“…First, the survey was based on caregiver report of ASD, without clinical validation and data are limited by parents' knowledge and recollection, which could impact the validity of the results as reflecting the true priority needs of those with ASD. While not the gold standard in ascertainment, several large scale family caregiver surveys have used caregiver report of official diagnosis and other variables [Kogan et al, ; Lin, Yu, & Harwood, ; Totsika et al, ; Shattuck, Narendorf et al, ] and a verification study showed reliability of diagnosis by caregivers [Daniels et al, ]. Second, our data was collected by convenience sampling using primarily online methods, which may have created barriers to participation for some families.…”
Section: Discussionmentioning
confidence: 99%
“…First, the survey was based on caregiver report of ASD, without clinical validation and data are limited by parents' knowledge and recollection, which could impact the validity of the results as reflecting the true priority needs of those with ASD. While not the gold standard in ascertainment, several large scale family caregiver surveys have used caregiver report of official diagnosis and other variables [Kogan et al, ; Lin, Yu, & Harwood, ; Totsika et al, ; Shattuck, Narendorf et al, ] and a verification study showed reliability of diagnosis by caregivers [Daniels et al, ]. Second, our data was collected by convenience sampling using primarily online methods, which may have created barriers to participation for some families.…”
Section: Discussionmentioning
confidence: 99%
“…a particular genetic syndrome). Similar processes have been used to ascertain developmental disability in past parent report surveys of youth and young adults with ASD and ID (Daniels et al 2011;Kogan et al 2008Kogan et al , 2009Lin et al 2012;Totsika et al 2011;Weiss & Burnham Riosa 2015).…”
Section: Participantsmentioning
confidence: 99%
“…[7,8] The barriers to health care access are further exacerbated for children with ASD from immigrant families with limited English proficiency (LEP). [9] Parental LEP has been associated with risks of adverse outcomes in children’s health and disparities in medical and oral health, access to care, and use of services with challenges in understanding clinical evaluation results, prescription instructions, follow-up appointments, referral to specialist and therapy-related documents. [10-12]…”
Section: Introductionmentioning
confidence: 99%